DOI acquisition by UFGD Portal of Scientific Journals and the search for new indexers - Silva Filho, Givaldo Ramos da; Garcia, Rodrigo Garófallo; Amaral, Cynara Almeida (Ciência da Informação em Revista, 2019)
This paper aims at presenting a case study about the work developed by the Publisher of Federal University of Grande Dourados (UFGD) regarding the UFGD Portal of Scientific Journals. The UFGD Publisher’s main goal was to improve the journals’ quality and disseminate the university scientific production. It tells the UFGD Publisher experience with DOI (Digital Object Identifier) acquisition through CrossRef/PILA (Publisher International Linking Association) and discusses the administrative and technological procedures involved in this process. This paper also brings information on how the journals available on UFGD Portal were adapted to the requirements of several national and international databases and directories (indexers), such as the Directory of Open Access Journals (DOAJ).